2020
DOI: 10.3389/fphar.2020.553690
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Alleviated Bleomycin-Induced Pulmonary Fibrosis Partly by Rescuing Alveolar Epithelial Cells From Senescence

Abstract: Idiopathic pulmonary fibrosis is an aging-associated disease, satisfactory therapies are not yet available. Accelerated senescence of alveolar epithelial cells plays an important part in Idiopathic pulmonary fibrosis pathogenesis. Fisetin (FIS) is a natural non-toxic flavonoid, which has many pharmacological functions. However, the role of FIS in pulmonary fibrosis has not been established. In this study, we found that FIS treatment apparently alleviated BLM-induced weight loss, inflammatory cells infiltration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Our in vivo experiment showed that both sacubitril/valsartan and valsartan could effectively inhibit the expression of TGF-β1 and p-Smads in the infarcted area. Our results have been further confirmed by a recent study by Zhang W et al, who found in rats with heart failure with preserved ejection fraction induced by high-salt diet that, sacubitril/valsartan effectively alleviated the symptoms probably by inhibiting fibrosis via the TGF-β1/Smad3 signaling pathway (Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Our in vivo experiment showed that both sacubitril/valsartan and valsartan could effectively inhibit the expression of TGF-β1 and p-Smads in the infarcted area. Our results have been further confirmed by a recent study by Zhang W et al, who found in rats with heart failure with preserved ejection fraction induced by high-salt diet that, sacubitril/valsartan effectively alleviated the symptoms probably by inhibiting fibrosis via the TGF-β1/Smad3 signaling pathway (Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, fisetin administration reduced the high transcription level of IL-6 in the hippocampus of MRL/lpr mice. Fisetin treatment causes a reduction of the transcription level of IL-6 in senescent cells in pulmonary fibrosis and aging-related pathology ( 40 , 66 ). Although the varied and complex pathogenic pathways complicate the development of NPSLE therapies, our data indicate that fisetin treatment targeted specifically to NPSLE senescent neural cells results in inhibition of SASP factors such as type-I interferon and IL-6, suggesting that fisetin is a candidate NPSLE therapeutic.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of Fisetin on aged wild-type mice reduced senescence markers in the fat, spleen, kidney, liver, and a subset of cell types in the adipose tissue, and its long-term administration on wild-type mice late in life improved tissue homeostasis, suppressed ageing-associated diseases like osteoporosis, and extended their median and maximum lifespan [ 152 ]. Fisetin has also been demonstrated to rescue bleomycin-induced pulmonary fibrosis in mice by relieving senescence in alveolar epithelial cells [ 153 ].…”
Section: Therapeutic Significancementioning
confidence: 99%